(untitled) (Bangladesh Journal of Botany, 2015)
Amount of polyphenols, flavonoids, anthocyanins in ethanol extracts and antioxidant activity of both ethanol and lipophilic extracts of common leafy vegetables in Bangladesh were compared. Among the 12 leafy vegetables, Ipomoea aquatica Forssk. showed the highest content of total polyphenols (38.9 mg gallic acid equivalent (GAE)/g extract) and flavonoids (23.2 mg (+)-catechin equivalent (CE)/g extract). Highest anthocyanins content was found in Amaranthus gangeticus L. (1.15 ?mol/g extract) followed by Pisum sativum L. (0.85 ?mol/g extract). Ethanol extracts of Brassica campestris L., Enhydra fluctuans Lour., I. aquatica, Lagenaria siceraria (Mol.) Standl. and P. sativum exhibited high DPPH free radical scavenging activity with IC50 of 104.2, 85.5, 26.9, 125 and 68.5 ?g/ml, respectively whereas for the same lipophilic pentane extracts of Basella alba L. showed the lowest (68.4 ?g/ml) IC50 followed by I. aquatica (70.4 ?g/ml), E. fluctuans (75.7 ?g/ml), L. siceraria (78.3 ?g/ml) and B. campestris (80.6 ?g/ml). I. aquatica also showed the highest NO free radical scavenging followed by B. campestris and B. alba. Highest reducing power (O.D. = 1.7) was observed for I. aquatica followed by P. sativum (O.D. = 1.12), B. alba (O.D. = 0.86) and L. siceraria (O.D. = 0.72) at 400 ?g/ml extract. They also displayed high total antioxidant capacity. Therefore, the top five potential leafy vegetables consist of both hydrophilic and lipophilic antioxidant(s), the order being I. aquatica > B. campestris > B. alba > P. sativum > and L. siceraria. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22723 Bangladesh J. Bot. 44(1): 51-57, 2015 (March)